ElectromyoFigureic Evaluation of Functional Adaptation of Patients with New Complete Dentures - Shala, Kujtim Sh. (Int J Dent, 2018)
OBJECTIVE: The objective of this study was to evaluate the level of adaptation of patients to newly fitted complete dentures in their dominant and nondominant sides, by means of ElectromyoFigureic signals. MATERIALS AND METHODS: Eighty-eight patients with complete dentures were evaluated in the study. Masticatory muscle (masseter and temporal) bioelectric activity of the patients with complete dentures was recorded at maximum intercuspal relation. Parametric statistical data were analyzed with one-way repeated measures ANOVA test. RESULTS: Measurement time was significantly different for both dominant (DS) and nondominant (NDS) sides: FΣs-DS = 21.51, p=0.0001; FΣs-NDS = 13.25, p=0.0001. Gender was also significantly different: FΣs-DS-gender = 41.53, p=0.001; FΣs-NDS-gender = 85.76, p=0.0001. The average surface area values showed significant difference in females. Prior experience with dentures showed no significant difference for both sides of mastication: FΣs-DS-experiences = 1.83, p=0.1772; F Σs-NDS-experiences = 3.30, p=0.0697. CONCLUSION: The planimetric indicators of bioelectric activity of masseter and temporalis muscles at maximum physiological loading conditions are significant discriminators of the level of functional adaptation of patients with new complete dentures.